Hubungan Antara Self Esteem dengan School Bullying Pada Facebook Remaja SMA Negeri 4 Kendari - Zayana, Zayana; Jumaidin, La Ode; Jaya, Asrul (Laboratorium Ilmu Komunikasi, Fakultas Ilmu Sosial dan Ilmu Politik (FISIP) Universitas Ha, 2019)
The purpose of this study was to identify the relationship between self esteem and school bullying on Facebook teenagers in SMA Negeri 4 Kendari. This study uses the theory of Kosep Diri Agustiani, H and the research method used in this study is a quantitative research method with the population of this study that is students of SMA Negeri 4 Kendari with a sample of 30 respondents. The technique for determining informants in this study is purposive sampling technique. While the data collection techniques used are questionnaires and documentation. The results of this study can be concluded that (1) High self esteem will be more respectful of itself and also respected by others, conversely someone who has low self esteem will be more likely to be a victim of bullying. (2) Strength Self-esteem or (self esteem) has a very strong relationship with bullying behavior, can be seen from the results of the final calculation of data that has been taken using a questionnaire, which is accumulated using a questionnaire, where variables X = 23.36 and variables Y = 35.83 means that the dependent variable is higher than the independent variable, so the conclusion is that there is a very strong relationship between self-esteem and school bullying on the Facebook teenagers of SMA Negeri 4 Kendari. (3) Based on the average score of the results of the questionnaire above is the relationship between self-esteem and bullying behavior on Facebook teenagers of SMA Negeri 4 Kendari have a significant relationship, it can be seen from the scores between variables namely the presentation of variable X is lower than the variable Y, so the relationship between self-esteem and school bullying on Facebook for SMA Negeri 4 Kendari teenagers is closely related, but if the score of the independent variable (X) is higher than the score of the dependent variable (Y), then self-esteem with bullying behavior has no relationship between the two, and if the score variable X and variable Y have the same score, or series, so they don't have a relationship either. As the score on the results of a questionnaire that shows bullying behavior has a very strong influence on the level of self-esteem in high school adolescents.Keywords: Self Esteem, School bullying, Teenager Facebook